2020
DOI: 10.18488/journal.135.2020.51.18.43
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Investigation of the Impact of Exports on Economic Growth: Evidence from Nigeria, 1980-2016

Abstract: Exports Economic growth ARDL Toda Yamamoto Growth plans Nigeria. Contribution/ Originality: This study contributed to the existing literature through an evidence-based decision making for the sustenance/abolition of current export-driven economic growth and development policies in Nigeria. Again, it is one of the few studies that addressed the issue of endogeneity while examining the nexus between exports and economic growth in Nigeria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
3
4
0
Order By: Relevance
“…The unfavourable investment climate in Nigeria is one of the likely reasons for this result. This finding contravenes the submissions of Duru and Ehidiamhen (2018) but agrees with the finding of Duru, Okafor, Adikwu, and Njoku (2020) and Duru and Ezenwe (2020). In addition, military outlay exerted a positive relationship with economic growth.…”
Section: Results Of the Bounds Test For Cointegrationsupporting
confidence: 88%
See 2 more Smart Citations
“…The unfavourable investment climate in Nigeria is one of the likely reasons for this result. This finding contravenes the submissions of Duru and Ehidiamhen (2018) but agrees with the finding of Duru, Okafor, Adikwu, and Njoku (2020) and Duru and Ezenwe (2020). In addition, military outlay exerted a positive relationship with economic growth.…”
Section: Results Of the Bounds Test For Cointegrationsupporting
confidence: 88%
“…Another factor is the export of mainly primary products. This result corresponds with the suggestions of Rigobon and Rodrik (2005); Rodriguez and Rodrik (1999); Adhikary (2011);Bibi, Ahmad, and Rashid (2014); Qazi (2015); Olasode, Raji, Adedoyin, and Ademola (2015); Musila and Yiheyis (2015); Moyo, Nwabisa, and Hlalefang (2017); Moyo and Khobai (2018); Tyopev (2019); and Duru and Ezenwe (2020). However, the finding contravenes the suggestions of Nduka (2013); Olufemi (2004); Winters (2004); Sakyi (2011); Dao (2014); Ali and Abdullah (2015); Dabel (2016); Keho (2017); Yakubu and Akanegbu (2018); Elijah and Musa (2019) and Ajayi and Araoye (2019).…”
Section: Results Of the Long-run Relationshipsupporting
confidence: 87%
See 1 more Smart Citation
“…To sum up, as HHI increases, GDP per capita also fluctuates higher which denotes that export diversification has direct positive relationship with economic growth in Afghanistan in the period spanning from 2008-2018. The above finding is supported by (Agosin, 2007;Duru and Ehidiamhen, 2018;Naude and Rossouw, 2008;Noureen and Mahmood, 2014).…”
Section: Trend Analysis Of Gdp Per Capita and Export Diversificationmentioning
confidence: 68%
“…The results reveal a negative relationship between economic growth and exports and the reason for which might be that exports decrease domestic consumption. Furthermore, (Duru and Ehidiamhen, 2018) found that export diversification has a positive and insignificant relationship with economic growth. They also found that TOP has negative insignificant influence on economic growth.…”
Section: Empirical Literaturementioning
confidence: 99%